Uji Resistensi Antibiotik dan Deteksi Gen Plasmid IncHI1 Salmonella typhi Isolat Jayapura - Rini S. Kelanit; Dirk Y.P. Runtuboi; Tri Gunaedi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
The research on antibiotic resistance test and detection of gene Plasmid IncHI1 1 Salmonella typhi isolates of Jayapura have been conducted in January to August 2015. The purpose of this study is to determine antibiotic resistance patterns and detect the presence ofS. typhi IncHI1 plasmid genes in Jayapura.The method of study was the laboratory analytic where ninety two samples were culture tested and S. typhi identified was tested using disc diffusion method of Kirby Bouer to see any resistance toward 18 antibiotics. Plasmids of S. typhi then were extracted using method of Kado-Liu. To ensure the presence of S. typhi DNA, the testof flagellin gen detection had been done using Nested PCR followed by gene Inchi1 S. typhi detection. The results showed that among 8 isolates of S. typhi, there has been a Multi Drug Resistant (MDR) of 7 samples (87.5%) with varying resistance patterns where the most resistant antibiotics are Amoxicillin 100% (8 isolates), Cefazolin 75% (6 isolates), Ampicillin 75% (6 isolates), Trimethoprim–Sulfamethoksazol 62.5% (5 isolates), Amikacin 62.5% (5 isolates), Gentamicin 50% (4 isolates) and Ampisillin–Sulbactam 50% (4 isolates). The most sensitive antibiotics is Meropenem is 87.5% (7 isolates). PCR test results showed that there were no genes of IncHI1 S. typhi in Jayapura.Key words: Salmonella typhi, gen IncHI1, antibiotic resistance, Jayapura.